A G protein-coupled receptor dimer imaging assay reveals selectively modified pharmacology of neuropeptide Y Y1/Y5 receptor heterodimers - Kilpatrick, Laura E.; Humphrys, Laura J.; Holliday, Nicholas D. (ASPET, 2015)
The ability of G protein-coupled receptors (GPCRs) to form dimers, and particularly heterodimers, offers potential for targeted therapeutics with improved selectivity. However, studying dimer pharmacology is challenging, because of signaling cross-talk or because dimerization may often be transient in nature. Here we develop a system to isolate the pharmacology of precisely defined GPCR dimers, trapped by bimolecular fluorescence complementation (BiFC). Specific effects of agonist activation on such dimers are quantified using automated imaging and analysis of their internalization, controlled for by simultaneous assessment of endocytosis of one coexpressed protomer population. We applied this BiFC system to study example neuropeptide Y (NPY) Y1 receptor dimers. Incorporation of binding-site or phosphorylation-site mutations into just one protomer of a Y1/Y1 BiFC homodimer had no impact on efficient NPY-stimulated endocytosis, demonstrating that single-site agonist occupancy, and one phosphorylated monomer within this dimer, was sufficient. For two Y1 receptor heterodimer combinations (with the Y4 receptor or β2-adrenoceptor), agonist and antagonist pharmacology was explained by independent actions on the respective orthosteric binding sites. However, Y1/Y5 receptor BiFC dimers, compared with the constituent subtypes, were characterized by reduced potency and efficacy of Y5-selective peptide agonists, the inactivity of Y1-selective antagonists, and a change from surmountable to nonsurmountable antagonism for three unrelated Y5 antagonists. Thus, allosteric interactions between Y1 and Y5 receptors modify the pharmacology of the heterodimer, with implications for potential antiobesity agents that target centrally coexpressed Y1 and Y5 receptors to suppress appetite.